Penyusunan Jadwal Induk Industri dengan Menggunakan Metode Simpleks Guna Meminimalkan Biaya Produksi - Murti Astuti; Ifa Yuliana (Department Industrial Engineering, University of Muhammadiyah Malang, 2001)
PT. Industri Sandang Nusantara Pata! Secang Magelang is some factory that regarding in manufactur sector which thread producting. For this time the factory have a problem with stacking same kind of product and in the other way less another product. This case cause that factory use product scheduling based on experience and reckoned of selling in last period. Connected with this problem, the case is how to make a good schedule in order that factory could be completing consumer demand and decided some main product schedule with simpleks methode.The articulate in factory for this time is reguler employee 65 persons. If reguler employee is not enaugh, then there are overtime job (maximal 2 hour/days), and if still not enaugh too, then used subcontract. Based on capacity of production, the number of maximal employee are 70 personsAccording to teoritis, with using of forecasting and agregat planning, the factory's problem can be done. This forecasting used to productin supossing in about to many periods. With use simpleks methode can be planning the number of employee. In order that, the main production can be made.Analyst result get that demand fluktuation for R 30/1, PR 30/1 products use Moving Average Linear Trend (3) methode, R 24/ 1, R I 11, PR 40/l products using Moving Average Linear Trend (5) methode, PR 45/l product using Linear Regression methode. Value analyst with based on forecasting result for future 12 periods, supposed that factory will pay for Rp. 460.340.000,• After applying Linear Programming giftotal cost Rp. 450.164.576,-. Thrifting Rp. 10.175.424,- or 2,2%. Sensitivity analyst made cost to be Rp. 448.651.040,-, thrifting Rp. 11.688.960,- or 2,5% at the number of regular employees 66 persons.